Role-of Ultrasound in Diagnosis of Acute Appendicitis - Ahmed, Hiwa O.; Arif, Tahir; Shalli, Alla Abdulkadir (Sulaimani Journal for Pure and Applied Sciences, 2007)
In this work the authors have tried a prospective study over 5 years to evaluate the role ofultrasound, in non selected groups of patients rvith-lowir abdominal pain & suspicion of acute appendicitis, all the ultrasound examinations done by two ultrasonographists. Although ultrasound is a simple, cost-effectivi, non-invasive investigation with high acceptance by the patients, itinical examination iemains a cornerstone of the diagnosis of acute appendicitis and it is superior to ultrasound examination in diagnosis of cases of acute appendicitis.
Keywords: Acute appendicitis; Ultrasound